HEPATOPROTECTIVE EFFECT OF GAMAVUTON-0 AGAINST D˗GALACTOSAMINE/LIPOPOLYSACCHARIDE-INDUCED FULMINANT HEPATIC FAILURE - Arief Nurrochmad; Ika Puspita Sari; Retno Murwanti; Sardjiman .; Triana Candraningrum; Dyah Afritasari; Devina Martina; Iren Wati Siahaan (Indonesian Journal of Pharmacy, 2012)
The  objective  of  this  study  is  to  determine  the  hepatoprotective  effect  of  GVT-0  (one  of  curcumin  analogues)  against liver  damage  in  rat-induced  D-galactosamine  (D-GalN)/lipopolysaccharide  (LPS)  as  a model  of fulminant  hepatitis.  In  the study D˗GalN/LPS  elevated  serum  GPT  activity  that  indicate  a particular occurrence of liver damage due to depletion of UTP and UDP-glucuronic acid. Administration of GVT-0 (10 mg/kg) showed decreased  enzyme  activity  of  SGPT/SGOT  but  had  no  effect  on serum  ALP  and  total  bilirubin  levels,  whereas  at  doses  of  20 and 40  mg/kg,  the  protective  effect  of  GVT-0  was  decrease.  The glutathione  content  in  the D-GalN/LPS  (0.76  ±  0.07)  mol/g  liver content was found lower than  controls  (0.90  ±  0.03)  mol/g  liver. Administration  of  GVT-0  dose  of  10,  20  and  40  mg/kg  restored glutathione content returned  to normal  levels. The results showed that treatment of GVT-0 showed no effect on TBARS and catalase activity.  Treatment  of  D-GalN/LPS,  indicating  the  trend  of increased  TNF-α,  although  statistically  not  significant,  while  the administration  of  GVT-0  showed  a  tendency  to  decrease  the concentration  of  TNF-α.  All  findings  of  the  results  indicated  that the GVT-0 mainly lower dose (10 mg/kg) showed hepatoprotective action  in rat  model  of fulminant  hepatitis induced  by D-GalN/LPS. The  results  indicated  that  the  mechanism  of  hepatoprotective effect  of  GVT-0  is  not  via  antioxidant  properties  of  GVT-0. However,  further  studies  are  necessary  to  explain  the  molecular mechanism of hepatoprotective effect of GVT-0.Key  words:  Gamavuton-0,  hepatoprotective,  fulminan  hepatitis, D˗galactosamine/LPS